2021
DOI: 10.1017/jns.2021.30
|View full text |Cite
|
Sign up to set email alerts
|

The burden of excessive saturated fatty acid intake attributed to ultra-processed food consumption: a study conducted with nationally representative cross-sectional studies from eight countries

Abstract: Cross-sectional nutritional survey data collected in eight countries were used to estimate saturated fatty acid intakes. Our objective was to estimate the proportion of excessive saturated fatty acid intakes (>10 % of total energy intake) that could be avoided if ultra-processed food consumption was reduced to levels observed in the first quintile of each country. Secondary analysis was performed of 24 h dietary recall or food diary/record data collected by the most recently available nationally representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
(56 reference statements)
0
12
0
1
Order By: Relevance
“…Even some proponents of NOVA and reducing UPF intake have suggested that the saturated fat, added sugar and sodium content of UPFs is important, despite this not being a core aspect of the UPF definition [ 28 ]. For example, authors have focussed on the impact of reducing UPF intake on changes in saturated fat, added sugar and sodium intake and dietary quality, and the subsequent benefit of these changes on disease risk [ 67 , 68 , 69 , 70 ]. Critics of NOVA/supporters of reformulation argue that any link between UPFs and adverse health is solely due to their nutrient content; that some UPFs are just high in saturated fat, added sugar and sodium and that some UPFs are not nutritionally inferior, with some studies showing no difference in saturated fat, added sugar and sodium intakes across extremes of UPF intake [ 64 , 71 , 72 ].…”
Section: Upf Removal or Upf Reformulation: The Case For ‘Healthy’ Upfs?mentioning
confidence: 99%
“…Even some proponents of NOVA and reducing UPF intake have suggested that the saturated fat, added sugar and sodium content of UPFs is important, despite this not being a core aspect of the UPF definition [ 28 ]. For example, authors have focussed on the impact of reducing UPF intake on changes in saturated fat, added sugar and sodium intake and dietary quality, and the subsequent benefit of these changes on disease risk [ 67 , 68 , 69 , 70 ]. Critics of NOVA/supporters of reformulation argue that any link between UPFs and adverse health is solely due to their nutrient content; that some UPFs are just high in saturated fat, added sugar and sodium and that some UPFs are not nutritionally inferior, with some studies showing no difference in saturated fat, added sugar and sodium intakes across extremes of UPF intake [ 64 , 71 , 72 ].…”
Section: Upf Removal or Upf Reformulation: The Case For ‘Healthy’ Upfs?mentioning
confidence: 99%
“…crisps, chocolate, biscuits), while being low in fruits and vegetables (Francis and Stevenson, 2013). The UPF found within the Western style diet are defined and classified by the NOVA food classification system as industrially manufactured foods containing added starches, vegetable oils, sugars, emulsifiers, foods additives (such as processed deli meats, biscuits, cakes, crisps, soft drinks) and consisting of substances such as chemicals that impact the nutritional quality of diets (Francis and Stevenson, 2013; Steele et al, 2021). These food products are highly prevalent in the food supply contributing up to 60% of total daily energy intake in several countries such as the US, Canada, UK, and Australia (Pagliai et al, 2021; Machado et al, 2019; Monteiro et al, 2019a).…”
Section: Adherence To Dietary Patterns and Cognitionmentioning
confidence: 99%
“…UPF also contain high amounts of trans fats to enhance palatability and texture. Evidence has highlighted that trans fats increase in adipose tissue with excessive consumption (Steele et al, 2021), and are also pro-inflammatory. Inflammation is associated with hyperinsulinemia, and in turn with insulin resistance, contributes to the development of hypertension and T2DM, all of which are markers for increased risk of cognitive decline (Silva Meneguelli et al, 2020).…”
Section: Adherence To Dietary Patterns and Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Реализация Стратегии повышения качества пищевой продукции (распоряжение Правительства Российской Федерации от 29.06.2016 № 1364-р «Об утверждении Стратегии повышения качества пищевой продукции в Российской Федерации до 2030 года») предусматривает обеспечение условий для производства пищевой продукции нового поколения с заданными характеристиками качества. Поэтому перед научно-исследовательскими организациями и предприятиями всех отраслей пищевой промышленности поставлены задачи по разработке и внедрению нового ассортимента изделий, способствующих повышению качества и структуры питания людей [2][3][4][5][6].…”
Section: Introductionunclassified